The influence of masticatory loading on craniofacial morphology: A test case across technological transitions in the Ohio valley - Paschetta, Carolina Andrea (2010)
Masticatory loading is one of the main environmental stimuli that generate craniofacial variation among recent humans. Experimental studies on a wide variety of mammals, including those with retrognathic postcanine teeth, predict that responses to masticatory loading will be greater in the occlusal plane, the inferior rostrum, and regions associated with the attachments of the temporalis and masseter muscles. Here we test these experimentally-derived predictions on an extinct human population from the middle and upper Ohio valley that underwent a marked shift from hunting-gathering to extensive farming during the last 3,000 years and for which we have good archaeological evidence about diet and food processing technology. Geometric morphometric methods were used to detect and measure the putative effect of diet changes on cranial shape independent of size. Our results partially confirm only some of the experimental predictions. The effect of softer and/or less tough diets on craniofacial shape seem to be concentrated in the relative reduction of the temporal fossa and in a displacement of the attachment of the temporal muscle. However, there were few differences in craniofacial shape in regions closer to the occlusal plane. These results highlight the utility of exploring specific localized morphological shifts using a hierarchical model of craniofacial integration. © 2009 Wiley-Liss, Inc.